Pengaruh Kontrasepsi Hormonal Pada Jaringan Periodontal: Telaah Literatur Sistematis dan Meta Analisis - Karin Tika Fitria; Mira Sri Gumilar; Yesi Nurmawi (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The health of periodontal tissue or tooth support is strongly influenced by a person's hormonal condition. In women of childbearing age, hormonal contraception is often an option, either orally, injected, or implanted. This study aims to analyze the effect of hormonal contraception on periodontal tissue. The manuscript deals with the effect of hormonal contraception on periodontal health with several indicators including loss of gum attachment (LoA), gingival index (GI), and pocket depth (PD). The three reviewers conducted a systematic review following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) protocol to obtain 9 articles that met the criteria. Statistical analysis to obtain the effect size was carried out using a random effect model with the help of Revman 5.3 software. The results of the meta-analysis showed that hormonal contraception provided a large size effect on pocket depth (SMD=2.16; CI=0.79, 3.3; I2=98%) and on the gingival index (SMD=4.37; CI=0.75,7.99; I2=99%) . Likewise for loss of attachment (SMD = 1.25; CI = 0.42.2.08; I2 = 98%), It can be concluded in this study that the use of hormonal contraception has an influence on periodontal health.